Cloud Storage Service Architecture Providing the Eventually Consistent Totally Ordered Commit History of Distributed Key-Value Stores for Data Consistency Verification - Beom-Heyn Kim (MDPI AG, 2021)
Cloud storage services are one of the most popular cloud computing service types these days. Various cloud storage services such as Amazon S3, DropBox, Google Drive, and Microsoft OneDrive currently support billions of users. Nevertheless, data consistency of the underlying distributed key-value store of cloud storage services remains a serious concern, making potential customers of cloud services hesitate to migrate their data to the cloud. Researchers have explored how to allow clients to verify the behavior of untrusted cloud storage services with respect to consistency models. However, previous proposals are limited because they rely on a strongly consistent history server to provide a totally ordered history for clients. This work presents Relief, a novel cloud storage service exposing an eventually consistent totally ordered commit history of the underlying distributed key-value store to enable client-side data consistency verification for various consistency models. By empirically evaluating our system, we demonstrate that Relief is an efficient solution to overcome the limitation of previous approaches.